Islamic Law's Impact on Wives, Children, and Wealth in Contract Marriages - Lumingkewas, Jitha Kemala Putri (Damhil Law Journal, 2022)
The purpose of this article is to find out the impact of Islamic law on wives, children, and property in contract marriages.Â  In this writing, the author uses a normative research method where this method is a legal research method that is carried out by examining library materials or secondary data. The results of this study indicate that the legal arrangement of contract marriage (nikah mutah) in the perspective of the Marriage Law is an invalid marriage and has no legal force, the legal consequences of contract marriage on the position of the wife and children are that the wife must carry out all obligations as a wife and the status of the child born is a child born illegally, because the marriage of his parents is not registered in a legal marriage. If the marriage ends with a contract marriage, then there is no division of joint property, even though the property was produced during the marriage. In addition, there is no right of inheritance from the contract wife to the contract husband.